Determinants of secondary prophylaxis for childhood rheumatic heart disease in Ethiopia: A qualitative study of children and caregivers - Eshetie Melese Birru; Kevin T. Batty; Laurens Manning; Stephanie L. Enkel; Brioni R. Moore (PLoS ONE, 2026)
Background Rheumatic heart disease (RHD) remains a major public health challenge in Ethiopia, particularly among children. Monthly intramuscular benzathine penicillin G (BPG) is the cornerstone of secondary prophylaxis, yet adherence and delivery are suboptimal. This study explores the lived experiences of children and adolescents with RHD, capturing their direct voices and those of their caregivers to understand determinants of secondary prophylaxis uptake. Methods A qualitative descriptive study was conducted from May to July 2022 in four Ethiopian public hospitals providing RHD care. Focus group discussions were held with children living with RHD (C-RHD) and their caregivers to explore barriers and facilitators of BPG delivery. Audio recordings were transcribed, translated, and thematically analysed using the framework method, with findings mapped onto the Capability, Opportunity, Motivation, Behaviour (COM-B) model. Results Forty-two participants (30 C-RHD, 12 caregivers) identified five interrelated determinants of BPG delivery: structural barriers (geographic inaccessibility, transport costs, limited policies), organizational challenges (drug shortages, inadequate follow-up and counselling), therapeutic issues (painful injections, needle blockages, limited alternatives), provider-related concerns (fear of adverse reactions), and individual factors (misconceptions, psychological distress, adherence behaviours). Despite a preference for injectable BPG, some children received less effective oral antibiotics due to poor access. Participants emphasized the need for reliable BPG supply, dedicated providers, and strengthened patient support programs. Conclusions Strengthening patient/carer education, improving BPG formulations and access, and addressing resource gaps within healthcare systems are critical to enhancing adherence, preventing ARF/RHD, and improving patient outcomes.